An Appraisal of Soil Organic Carbon Content Availability Under Diverse Vegetation Cover in Delta State, Southern Nigeria - Edewor Akpezi Okiemute (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
Organic carbon availability is crucial for effective soil capability, suitability, and fertility potentials, which makes it a serious consideration among all soil parameters in the evaluation of soil nutrient availability and general carbon sequestration. This research article explored an appraisal of soil organic carbon content availability across diverse vegetation covers in Delta State, Southern Nigeria, including lowland rainforests, secondary regrowth, and wet grasslands. The study aimed to establish whether significant differences exist in organic carbon availability across the landscapes to determine soil suitability for functional utilitarian purposes. The methodology adopted was strictly a field survey where soil samples were collected in situ across the three different landscapes at depths of 0-15 cm (not meters), which is the zone of nutrient uptake and activity. A total of 90 samples, with 30 collected from each landscape, were drawn based on systematic stratification. The one-way ANOVA revealed no significant difference in soil organic carbon content across the studied landscapes (p = 0.54, p > 0.05), leading to the acceptance of the null hypothesis. This indicates that the landscapes share similar soil fertility and nutrient availability, supporting their equal suitability for agricultural uses, particularly for arable crop production and precision farming in wet grasslands.